Pemetaan Digital dan Pengelompokan Lahan Hijau di Wilayah Provinsi Riau Berdasarkan Knowledge Discovery in Databases (KDD) dengan Teknik K-Means Mining - Mustakim Mustakim (UIN Sultan Syarif Kasim Riau, 2012)
Development of technology more rise in all circle, in education, instance and in interprise One oftechnology are internet and mapping. Significant function of map is giving information to reader or digitalaccess, in this case, digital mapping for grouping green land in Riau by using KDD technique data mining.Green land the topical is forest. This system give information like territory map grouping in Riau, withoutput a digital maps green land, besides detail information every teritory. This system is developed byprograming language PHP with mapping in google maps. User from this system consist of admin, leaderand ordinary user based on every access rightfull authority.Keyword : Data Mining, Digital Mapping, K Means, Knowledge Discovery in Databases (KDD)